MODULAR FORMS-page51

# MODULAR FORMS-page51 - 47(iv Show that the expression...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 47 (iv) Show that the expression Qn−1 ν =1 ν ν ν ϑ00 ( n ; τ )ϑ 1 0 ( n ; τ )ϑ0 1 ( n ; τ ) 2 2 ϑ00 (0; τ )n−1 ϑ 1 0 (0; τ )n−1 ϑ0 1 (0; τ )n−1 2 . 2 does not change when τ is replaced with 2τ . (v) Show that Qn−1 ν =1 ν ν ν ϑ00 ( n ; τ )ϑ 1 0 ( n ; τ )ϑ0 1 ( n ; τ ) 2 2 ϑ00 (0; τ )n−1 ϑ 1 0 (0; τ )n−1 ϑ0 1 (0; τ )n−1 2 (−1) = 2 Q n−1 2 n−1 2 ` ν ν ν ϑ00 ( n ; τ )ϑ 1 0 ( n ; τ )ϑ0 1 ( n ; τ ) ´2 2 2 ϑ00 (0; τ )n−1 ϑ 1 0 (0; τ )n−1 ϑ0 1 (0; τ )n−1 ν =1 2 2 (vi) Prove the formula Q n−1 2 ν =1 ϑ00 ν ν ν ϑ00 ( n ; τ )ϑ 1 0 ( n ; τ )ϑ0 1 ( n ; τ ) 2 2 (0; τ )n−1 ϑ 1 n−1 ϑ 1 (0; τ )n−1 0 (0; τ ) 02 2 z 5.6 Let Λ = Zω1 + Zω2 . Set t(z ; ω1 , ω2 ) = ϑ 1 1 ( ω1 ; 22 =2 1−n 2 . ω2 ). ω1 (i) Show that t(z + ω1 ; ω1 , ω2 ) = −t(z ; ω1 , ω2 ), −πi t(z + ω2 ; ω1 , ω2 ) = −e 2z +ω2 ω1 t(z ; ω1 , ω2 ). (ii) Let ω1 , ω2 be another basis of Λ. Show that t(z ; ω1 , ω2 ) = Ceaz 2 +bz t(z ; ω1 , ω2 ) for some constants C, a, b. (iii) By taking the logarithmic derivative of both sides in (ii) show that a=− t (0; ω1 , ω2 ) t (0; ω1 , ω2 ) + , 6t (0; ω1 , ω2 ) 6t (0; ω1 , ω2 ) b= t (0; ω1 , ω2 ) , 2t (0; ω1 , ω2 ) and t (0; ω1 , ω2 ) ; t (0; ω1 , ω2 ) C= (iv) using (iii) show that ϑ 1 1 (0) a=− 22 2 6ϑ 1 1 (0)ω1 ϑ 1 1 (0) + 22 22 6ϑ 1 1 (0)ω1 2 22 and b = 0; (v) using the Heat equation (see Exercise 3.8) show that ϑ 1 1 (0) 22 ϑ 1 1 (0) 22 where τ = ω2 . ω1 = 12πi d log η (τ ) , dτ ...
View Full Document

## This note was uploaded on 01/08/2012 for the course MATH 300 taught by Professor Ontonkong during the Fall '09 term at SUNY Stony Brook.

Ask a homework question - tutors are online